Students' Mathematics Learning Achievement at Vocational School: An Experimental Study of Using Quizizz-Based E-SW - Sumale, Lufna; Abdullah, Abdul Wahab; Takaendengan, Bertu Rianto (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study's objective is to determine the effect of the use of Electronic Student Worksheets (E-SW) based on Quizizz on student learning achievement. The type of research used in this study is quantitative, and it uses an experimental method with a pretest-posttest control group design. Where in this research design, students are given a pre-test first to determine students' initial knowledge, and the last is provided a post-test. The study's population was 87 students from grade X at Public Vocational School 1 Bulango Selatan. The research sample was chosen at random from two grades: grade X Askep B was used as an experimental grade to test E-SW based on Quizizz, and grade X Askep A was used as a control grade to compare how E-SW and textbooks are used. The findings showed that in the inferential analysis, pretest-posttest, both sets of data are normally distributed and homogeneous. This led to the covariance test (ANCOVA), which showed that H0 was rejected and H1 was accepted. So the results of this study show that student learning achievement are higher after being taught using E-SW based on Quizizz compared to using regular student worksheets. This means that using electronic student worksheets based on Quizizz has a positive influence on students' mathematics learning achievement.